Learning style preferences of senior secondary school economics students (2020)
Despite the increasing number of candidates offering economics in senior secondary schools and the importance of the subject to entrepreneurship education, performance of students in public examinations, such as the Senior School Certificate Examination (SSCE), in the subject has been low and oscillating between, below-average and average performance. The cause of this oscillating and sometimes poor learning outcome has been attributed to many factors; chief among them is the background characteristics of students- of which learning style is one. To the best of the knowledge of the researcher, few studies have been done in the area of learning style of senior secondary school economics students. This prompted the researchers to undertake this survey research- to investigate the dominant learning style of high school economics students; so as to assist teachers to put in place teaching methods/aids that accentuate teaching efficiency and better learning outcomes. The Kolb learning style inventory (KLSI) version 3.1(2005) was administered to a sample of 560 senior secondary 1, 2 and 3 students, from a population of senior secondary school students offering economics in Ogun state, Nigeria. The data obtained were subjected to descriptive statistics- frequency counts and percentages and chi-square tests. Findings of the study reveal an even distribution of the four selected learning styles, among the sample used for the study. However, Reflective learning style was the most prevalent style, (27%) followed by both Abstract learning style (25%) and Concrete learning style (25%), the Active learning style being the least, (23%). In addition, there was no significant association between class (X2t 0.384 and P=0.999), gender (X2, 0.220 and P=0.974) and subject area specialization (X2, 1.243 and P=0.999) of students and learning styles. It is recommended that teachers of high school economics adopt multiple teaching methods/aids so as to meet the diverse learning styles of students.